Konut ve Çatılı İşyeri Kiralarında Sözleşmenin Kiraya Verenden Kaynaklanan Sebeplerle Dava Yoluyla Sona Ermesi - Güler, Zeynep (Seçkin Yayıncılık, 2016)
6098 sayılı Türk Borçlar Kanunu konut ve çatılı işyeri kiralarının sona ermesini “bildirim yoluyla” ve “dava yoluyla” olmak üzere iki başlık altında düzenlemiştir. Bunlar konut ve çatılı işyeri kira sözleşmelerine özgü sebepler olup sınırlı sayıdadırlar. Dava yoluyla sona erme ise “kiraya verenden kaynaklanan” ve “kiracıdan kaynaklanan” sebepler olmak üzere ikiye ayrılır. Kiraya verenden kaynaklanan sebepler, kiraya verenin veya yeni malikin konut veya işyeri ihtiyacı ve kiralananın yeniden inşası veya imar amaçlı onarımı, değiştirilmesi ve genişletilmesidir. Çalışmamız kapsamında kiraya verenden kaynaklanan sona erme sebepleri ele alınacaktır.

The Turkish Code of Obligations regulates the termination of the lease agreement regarding dwelling and work place under two different division such as “through notice” and “through litigation”. These reasons are special to lease of dwelling and work place and they are counted according to numerus clausus principle. Termination through litigation is also divided in two sections; “the reasons regarding the leaser” and “the reasons regarding the lessee”. The reasons regarding the leaser are the need for a dwelling or workplace of the leaser or the new owner and rebuilding or restore of the contract’s subject. In this study, the reason regarding the leaser are explained.
The Termination of the Lease Contracts Regarding Dwelling and Workplace Through Litigation due to the Reasons Concerning the Leaser
Keywords: 6098 sayılı Türk Borçlar Kanunu; Konut ve çatılı işyeri; Kira Sözleşmesi; Dava yoluyla sona erme; Kiraya verenden kaynaklanan sebepler; Turkish Code of Obligations; Dwelling and Workplace; Lease Contract; Termination Through Litigation; The Reasons Regarding the Leaser